Criminal Responsibility among Murderer Presented to Forensic Committee in Al-Rashad Training Hospital/ Forensic Department, 2016-2017.. - Basheer F. Hummadi1 Firas A. Al-Kadhimi1, Ghazi A. Al-mashhadani1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The insanity defense, also known as the mental disorder defense, is a defense by excuse in a criminal case, arguing that the defendant is not responsible for his or her actions due to an episodic or persistent psychiatric disease at the time of the criminal act. This is contrasted with an excuse of provocation, in which defendant is responsible, but the responsibility is lessened due to a temporary mental state. The aim of current study was to find out the results of criminal responsibility assessment for the murderers and related mental illness as well as to study a sociodemographic and personal criterion for murderers. Methods: The study was conducted in AL-Rashad Hospital, forensic department in Baghdad. It was a descriptive retrospective study. Case files of (70) murderers, examined by the forensic committee during the period from 1st, January 2016 till 31st, December 2017, were studied. Comprehensive data were collected and analyzed by the SPSS version 23. Results: The study showed that murderers were mainly young adults within age group (20-40) years that were married, illiterate/low educational level and had no job or unstable type of jobs. About 30% of victims were 1st degree relative and 30% of them were family in law. The main weapon was used in the murder was gun (45.7%) and knife (40%). According to murderers who presented to the committee, about 38.6% had no mental illness, 17.1% had personality disorder, 32.9% had psychotic disorders and 8.6% had neurotic disorders. The majority of murderers (52.9%) presented to committee were considered responsible, 8.6% had partial responsibility and 28.6% considered irresponsible. Conclusions: This study showed that about more than half of murderers presented had full criminal responsibility and insanity defenses were succeeded only in one third of the cases. The studied murders appeared to be obvious among young adult age groups, with no job or unstable financial resources, and illiterate or had low educational level. The victims were more likely to be from 1st degree relatives or family in-law. The available weapon (gun and knife) was mostly used.